Surgical Decompression or Corticosteroid Treatment of Indirect Traumatic Optic Neuropathy: A Randomized Controlled Trial - Chen, Hsin-Hung; Lee, Min-Chao; Tsai, Chia-Hsuan; Pan, Chun-Hao; Lin, Yu-Te; Chen, Chien-Tzung (Annals of plastic surgery, 2020)
Traumatic optic neuropathy (TON) is a rare cause of severe permanent visual impairment after injury. Traumatic optic neuropathy may occur due to sharp trauma (direct injury) that damages the optic nerve directly or due to damage from the transmitted forces after a concussive blow to the head or orbit (indirect injury). The management of indirect TON remains controversial. Either surgical decompression or mega dose corticosteroid is used for managing indirect TON. However, no consensus exists regarding the definitive treatment. We designed a randomized controlled trial study to investigate this issue. Only patients with indirect TON and normal vision before the injury were enrolled. The patients' data were recorded, and fine cut facial computed tomography scan was performed to exclude those with retrobulbar hematoma. All the study subjects were randomly allocated to either the mega dose steroid (30 mg/kg stat and 15 mg/kg every 6 hours for 3 days) group or the surgical decompression group. The patients were followed up at 1 week, 1 month, 3 months, 6 months, and 9 months. During each follow-up, the Snellen visual acuity (VA), visual field, color change, fundus findings, and intraocular pressure were evaluated. These data were compared and analyzed using the Mann-Whitney U test and odds ratio. The short form questionnaire was used to analyze the lift quality difference between the two groups. Thirty patients were enrolled, 12 in the surgical group and 18 in the steroid treatment group. There were no significant differences in the improvement rate, improvement degree, and life quality between the groups. However, the odds ratios are 5, 10, 2.5, and nonavailable in the cutoff points of no light perception (NLP), light perception (LP), hand movement, and counting finger in surgery group. In steroid group, they are 1, 1, 1, 1.83 in each cutoff points. Patients with better VA than NLP had better life quality than those with NLP VA (P = 0.005). Other cutoff point groups had no significant difference. Patients with worse initial VA (eg, NLP and LP) had a higher chance of benefiting from surgical treatment and experiencing improvements in the life quality.